2020
DOI: 10.1245/s10434-020-09398-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of In-Person Versus Virtual Interviews for Complex General Surgical Oncology Fellowship in the COVID-19 Era

Abstract: Background. In the era of coronavirus disease 2019 (COVID-19), many Complex General Surgical Oncology (CGSO) fellowship programs implemented virtual interviews (VI) during the 2020 interview season. At our institution, we had the unique opportunity to conduct an inperson interview (IPI) prior to the pandemic-related travel restrictions, and a VI after the restrictions were in place. Objective. The goal of this study was to understand how the VI model compares with the traditional IPI approach. Methods. Online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 14 publications
1
50
1
Order By: Relevance
“…An overview of all these prior studies combined highlights that surgical training programs, in particular, disproportionately favor in-person interviews (23,25,29,30,32,34). When looking carefully at their results, though, the majority of the subjective data show that web-based virtual interviews are effective for the majority of applicants in allowing them to learn about the educational environment and the culture (Table 2), see comments).…”
Section: Do Virtual Interviews Work? a Look Backmentioning
confidence: 99%
“…An overview of all these prior studies combined highlights that surgical training programs, in particular, disproportionately favor in-person interviews (23,25,29,30,32,34). When looking carefully at their results, though, the majority of the subjective data show that web-based virtual interviews are effective for the majority of applicants in allowing them to learn about the educational environment and the culture (Table 2), see comments).…”
Section: Do Virtual Interviews Work? a Look Backmentioning
confidence: 99%
“…Despite the lack of differences in variabilities in virtual interviews compared to-in person interviews, prior studies showed that most candidates consider the in-person interview experience to be better than virtual interview experience, and in-person interview candidates felt better acquainted with the faculty and current trainees compared to virtual interview candidates. [13] Furthermore, in-person interview candidates were also more likely to agree that the interview experience was su cient to allow them to make a ranking decision, [14] while many virtual interview candidates felt that they did not get an adequate understanding of the program. [15] In summary, in our clinical glaucoma fellowship program, a change from one-to-one interview resulted in less candidate ranking variabilities between interviewers paired in the rooms, which may decrease the candidates' opportunities to represent themselves satisfactorily.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 6 were adjuncts 19 -24 to the face-to-face interview while 12 were replacements. 25 -36 Studies used Skype 19,21,24,25,26,27,28,30 Facetime 19 , Zoom 31,32,34,35,36 or a combination of two platforms. 22,23,29 Eleven studies provided additional information outside the virtual interview itself including a video tour of the facility, video tour of the surrounding communities, Google hangout session with current residents, electronic brochures, and resident contact information to ask additional questions if interested.…”
Section: Virtual Panel Interviewmentioning
confidence: 99%